Using the SAS Method with Letter Card Media to Improve Beginning Reading Skills at SDN 2 Kunden - Sri Sunarsih (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The implementation of the research based on interviews and observations of classroom teachers, there are still grade I students of SDN 2 Kunden whose initial reading skills are not yet fluent. The purpose of this study was to determine whether by using the SAS method and the letter media, initial reading skills have been improved. The classroom action research (CAR) approach developed by Kemmis and McTaggart was used in this study. This study uses a qualitative descriptive approach as its methodology. To collect the research data used observation, interviews, and documentation. The findings of this study indicate that using the SAS method and letter card media can improve the basic reading skills of grade I students, especially the results of the assessment in the first cycle, the percentage of completeness reaches 76%, then in the second cycle there is an increase to 95,2%. Therefore, it can be said that the SAS method used together with letter card media is effective in improving student’s initial reading skills.